Fundlator / Siti Fatimah Ahmad ... [et al.] - Ahmad, Siti Fatimah; Amrin, Fatimah Azzahra; Mohd Zakir, Aniq Zikry Hakim; Abidin, Mohd Isham (Universiti Teknologi MARA, Kedah, 2023)
Fundlator is an application that is related to fundraising. Through this application, it can help people or animals that are in need. Basically, the application will collect donations from the users of this application and the money will be distributed to trusted agencies that are helping the homeless, cancer patients, stray animals, victims of natural disasters, and many more. Individuals that are in need can also get donations by filling up the form that is already prepared in the application and will be reviewed if they are eligible to get the fund or not. However, there are many crowdfunding scams issues that are being reported nowadays, some of the crowdfunding platforms on the internet may not be trustable which makes society feel doubts to donate. Therefore, the objective of this application is to provide a fundraising application that everyone can trust without having the fear of getting scams and at the same time create awareness of donating in society. Apart from that, this application also offers uniqueness, which will be a lucky draw that will be conducted quarterly with interesting prizes to users who donate the most to the application. By doing this, the users will feel appreciated, and it will encourage them to donate frequently. The benefit of this application is it can help to reduce other people's burdens in terms of money, and it also helps people free from scammers that always do fake fundraising to scam people. Other than that, this application is only eligible to Maybank users as it had collaborated with the bank. The users are only valid to make donations through their Maybank account. Lastly, the collaboration with Maybank will also help the application gain more trust from the user to achieve the objective of helping society.